Comparison Of Sharia Banking Performance Implementation Based On Maqashid Shariah Index In Sharia Banks In Indonesia And Malaysia - Safira Safira; Hadijah Hadijah (Journal of Islamic Economics and Social Science (JIESS), 2022)
This study aims to analyze the performance of Islamic banking in Indonesia and Malaysia. At present, the measurement of the performance of the Islamic banking industry uses only the measurement of financial ratios (which are oriented towards shareholders). This measurement is not enough. Islamic banking needs a new paradigm in terms of measuring its performance of the which is not only limited to financial ratios. This study Applies approach the maqashid shariah index as a measurement of sharia banking performance. This type of research used in this study is comparative research. The object of this research is the Islamic banking industry, there are eight Islamic banks in Indonesia and nine Islamic banks in Malaysia that meet the criteria. The type of the data used is secondary the data in the form of financial reports / annual reports Obtained from the official website of each bank. By using the different test analysis method, the F count for the MSI variables with variances assumed aqual (assumed that both variants are equal) is 2002 with a probability of 0117. Because the probability of the data> 0.05, it can be concluded that there is no significant difference in the variance in the performance comparison of data based on the MSI of Islamic Banks of Indonesia and Islamic Banks of Malaysia.